2015
DOI: 10.1111/pme.12767
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Pressure Pain Hypersensitivity in the Cervical Muscles in Women with Migraine

Abstract: This study showed generalized pressure pain hypersensitivity in the cervical musculature in women with migraine. Our findings provide support for the physical therapy treatment and evaluation of musculoskeletal cervical spine disorders in individuals with migraine and reinforce that all cervical muscles should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 26 publications
4
58
0
3
Order By: Relevance
“…PPTs were measured bilaterally at five test locations in a fixed, cyclic order with a 20 s interval between the measurements: 1) temporalis muscle (i.e., 1 cm lateral to the external angle of the orbit) [27], 2) paraspinal muscles C1 (i.e., 2 cm lateral of the midline of the neck, below the occipital bone), 3) upper trapezius muscle (i.e., midpoint between acromion and spinous process C7) [16,28], 4) extensor carpi radialis muscle (i.e, at 1/3 of the length of the underarm, distal to the elbow) and 5) tibialis anterior muscle (i.e., at 1/3 of the length of the lower leg, distal to the knee). The first three test locations are cephalic regions and the latter two are extra-cephalic regions.…”
Section: Mechanical Sensitivitymentioning
confidence: 99%
“…PPTs were measured bilaterally at five test locations in a fixed, cyclic order with a 20 s interval between the measurements: 1) temporalis muscle (i.e., 1 cm lateral to the external angle of the orbit) [27], 2) paraspinal muscles C1 (i.e., 2 cm lateral of the midline of the neck, below the occipital bone), 3) upper trapezius muscle (i.e., midpoint between acromion and spinous process C7) [16,28], 4) extensor carpi radialis muscle (i.e, at 1/3 of the length of the underarm, distal to the elbow) and 5) tibialis anterior muscle (i.e., at 1/3 of the length of the lower leg, distal to the knee). The first three test locations are cephalic regions and the latter two are extra-cephalic regions.…”
Section: Mechanical Sensitivitymentioning
confidence: 99%
“…Both migraine and tension-type headache have been associated with altered perception of electrical stimulation and pressure pain thresholds (Gierse-Plogmeier et al, 2009;Bezov et al, 2011;Andersen et al, 2015) and increased pericranial tenderness (Fernandez-de-Las-Penas et al, 2008;Bendtsen et al, 2016). In addition, generalized pressure pain hypersensitivity of the cervical muscles has been found in persons with migraine (Florencio et al, 2015). The coexistence of tension-type headache and neck pain in persons with migraine may be contributing factors to the development of increased allodynia and hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Although individuals with chronic migraine exhibited lower PPTs (more hyperalgesia) in fronto‐temporal areas (Fp1, Fp2) than those with episodic migraine, differences were small. Previous studies analyzing differences in pressure sensitivity in the trigemino‐cervical area in migraine did not differentiate between the episodic or chronic form . A previous study including a small sample size did not also find differences in PPT in the cervical muscles between women with episodic or chronic migraine .…”
Section: Discussionmentioning
confidence: 74%
“…4 In fact, static mechanical pain hyperalgesia, expressed as decreased pressure pain thresholds (PPTs), is a manifestation of sensitization of nociceptive pain pathways. Previous studies investigating differences in PPTs in the trigemino-cervical areas on migraine sufferers reported conflicting results since some studies observed lower PPTs within the migraine group compared to healthy people, [5][6][7][8] whereas others did not find such differences in pressure pain sensitivity. 9,10 Discrepancies between previous studies can be related to different aspects.…”
mentioning
confidence: 90%
See 1 more Smart Citation